Circulating Tumor Cells: A New Avenue for Clinical Management of Cervical Cancer - Divya Janjua; Apoorva Chaudhary; Nikita Aggarwal; Arun Chhokar; Joni Yadav; Tanya Tripathi; Udit Joshi; Alok Chandra Bharti (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Despite successful vaccination and cytological screening protocols, metastatic cervical cancer (CaCx) remains a significant health concern for women in low-resource countries. This is primarily due to the fact that the disease is often detected at advanced stages. The prognosis of metastatic CaCx, regardless of the geographical distribution, continues to be poor despite improvements in prevention, diagnosis, and treatment techniques. Unlike other malignancies, definite malignancy-specific markers for CaCx progression that could predict the treatment outcome do not exist. Recent developments suggest that circulating tumor cells (CTCs) possess stem cell properties and are important candidates to monitor the metastatic process. They offer a real-time opportunity to identify the stage of carcinogenic progression and subsequently classify patients accordingly. The potential of CTCs to predict minimum residual disease and chances of recurrence renders them as potential prognostic candidate. In the past decade, a number of studies have established the clinical correlation of CTCs with prognosis and diagnosis of various malignancies. A few studies based on detection and analysis of CTCs in CaCx have offered valuable information about the likelihood of local or distant relapses and progression-free survival. The present chapter provides a brief overview of biology of CTCs and existing label-dependent and label-free methods for their detection. The article emphasizes recent advancements and the development of CTCs as a clinico-pathological factor in CaCx. Lastly, it discusses the successes, challenges, and future prospects associated with CTCs for the clinical management of metastatic CaCx.